Assessing Circular Information Flow in Industrialized Construction: a framework for evaluating data for circular construction. Issue 1 (1st September 2022) - Berglund-Brown, J; Kedir, F; Riabova, A; Hall, D
Abstract: A circular economy offers a solution for improving both the efficiency and environmental impact of the built environment. As the construction industry transitions to a circular economy, adequate information flow is necessary to keep products in the value chain for as long as possible. Industrialized construction firms show high potential for a successful transition to a circular economy because of optimized information flow through the use of product platforms, the use of information communication technologies, and the integration of actors. However, there is no current framework to assess whether construction firms using industrialized construction methods have a circular information flow. In this research, four characteristics are identified as main descriptors of a circular information flow framework: Completeness, Availability, Accessibility, and Incorporation of Information into Business Strategy . Using the framework, industrialized construction firms are asked to self-assess their performance through pre-defined survey questions. The findings from sixteen industrialized construction firms reveal the need for more complete data about recyclability potentials of products and unique materials and product identifiers, with 47% of firms indicating they have insufficient information. The survey of companies also indicates a need for more feedback about the reuse, recycling, and remanufacturing phases to be available, with only 20% of firms gathering feedback about reuse, 13% about recycling, and 20% about remanufacturing. The stakeholders with the most consistent access to information about design and materials of a project are the manufacturer, engineer, architect, and assemblers. 13% of firms employed RFID tags. More accessibility of information is needed for actors outside of the firm. Additionally, only 13% of firms implemented a take-back strategy, emphasizing the need for incorporating these business strategies within the firm. 17% of firms, however, had CE in mind during strategic development, demonstrating the potential for CE adoption in industry. Finally, the paper discusses future opportunities for circular information flow, such as employing blockchain technology.